Investigating student agency and affordances during online virtual exchange projects in an ELF context from an ecological CALL perspective. (October 2022) - Hsieh, Ming-Hung; Chuang, Hsueh-Hua; Albanese, Dale
Abstract: Situated in a computer-assisted language-learning (CALL) context with English as a lingua franca (ELF), this qualitative case study of virtual exchange projects adopts an ecological perspective to investigate student agency in engaging with perceived affordances of the learning environment. Data collected through semi-structured interviews and student reflections were triangulated with instructor observations, researcher memos, and artifacts such as student-produced presentation slides and videos. Results of the study indicated that students engaged with diverse formations of affordances within the multimodal online environment. Particularly, students' agentive behaviors manifested through interactions with teacher and peer support as well as negotiation of collaboration between students of different sociocultural backgrounds. Pedagogical implications are provided for educators considering the implementation of student-centered, constructivist instructional practices via online virtual exchange projects along with theoretical and methodological suggestions for future research. Highlights: Intercultural virtual exchange has rich pedagogical potential for developing student agency. Perceived affordances are context-specific and contingent on interactions between diverse agents. Multimodal virtual exchange environment fosters students' agentive behaviors engaging integrated affordances. Student agency in the English as a lingua franca context is activated and enacted during virtual exchange projects. An ecological approach reveals the co-instantiative nature of linguistic, social, cultural, and digital affordances.